Decidere le origini, fare le storie e concluderle degnamente: Appunti per una postultima lezione - Attisani, Antonio (Mimesis Journal, 2018)
This would be what I would have said if I had held my last lesson before retirement. Fortunately for the students, this did not happen. What I would have tried to say, which is echoed in these pages, is that we must not consider "theatre" only what is now being staged by institutions. Theatre is the "root of all human culture", as Maestro Carlo Sini explains, and a shared and deeper knowledge of its protocols would have the effect not only of improving what it is seen on stage, but also of helping us to inhabit the world as a place and a time of knowledge.